Formas comunicantes: discurso visual e regimes de interação na espacialidade constituída pela linguagem digital - Rovigatti, Samantha Manfroni Filipin (2014)
This research presents a reflection on the communicative character and interactional relationships present in multidimensional spatiality - permeated and constituted by engendering between the physical and the digital. Understanding the architectural space as an important visual language that engages in housing, interact, affect, communication, the study seeks to answer as the informational and aesthetic layers constitute the materiality, showing communicative implications that can add value to the works, as visual texts. Since the analyzed architecture is inserted in urban space, incorporates up to discussion the contemporary city, marked by spatio-temporal acceleration and the incompleteness. The methodological basis for the analysis is consistent concepts of Plastic Semiotics, from the seizure of constituent cognitive data of the speech, in the plans of expression and content, aesthetics and concepts, which allow the examination elements and modes of manifestation of the sensible. The analytical bias focuses on spatio-temporal agency, establishing interaction rules and new modes of experience of spatiality. The selected visual texts carry interactivity and memory, respectively, as one of its main communication elements. From the perspective of analysis, research of informational and aesthetic layers, as well a providing an increase of communication and poetic order to architectural objects, still leads to the conclusion that the experience of multidimensional spaces does reflect the ways of life in contemporary society - age that adaptability is constant and that the body appears as the great communication link.